Ecocritical Analysis of “Tintern Abbey” “To A Skylark”, and “Lispeth”: Impact of Nature on Human Mind and Physique - Sayeef Ahmed (University of Chitral Journal of Linguistics and Literature)
Eco-critical literary writing is a fairly new trend in the world. However, even before the concept of ecocriticism began to develop, famous Western poets and writers started producing their works that dealt with the issues of ecocriticism. Ecocriticism sheds light on the relationship of humans with the natural world and the animal world and discusses issues related to this relationship. In this study, William Wordsworth’s poem “Tintern Abbey,” Percy Bysshe Shelley’s “To a Skylark,” and Rudyard Kipling’s short story “Lispeth” have been taken into consideration for an eco-critical analysis. This study has tried to investigate how nature can impact the physique and soul of human beings and how ecocritical literature projects the impact and delineates nature’s relation with humans. To conduct the study, the concept of ecocriticism and its development have been discussed initially. Eventually, the texts chosen for this study are analyzed and discussed to examine and determine the impact of nature on the human physique and mind. Besides the textual analysis, some empirical research findings of the related field wherein nature's impact on humans is studied have been shown and discussed at different stages of this study to justify whether the poet and writers' claim of the positive effect of nature on humans is true.